Saudi clerics and Shīʿa Islam - Ismail, Raihan (Oxford University Press, 2016)
Acknowledgements -- A note on conventions -- Introduction -- 1. The significance of the 'ulama': a historical overview -- 2. Origins: the Shia faith -- 3. The theological convictions of the Saudi 'ulama' towards the Shi'a -- 4. The Saudi 'ulama' and the internal Shi'a threat -- 5. The Saudi 'ulama' and the external Shi'a threat: the case of Iran -- 6. the Saudi 'ulama' and the external Shi'a threat: the case of Bahrain, Iraq and Yemen -- Conclusion -- Glossary -- Notes -- Bibliography -- Index